System Monitoring Tools Version 2.0 (SMTv2) green computing (power management) / Nurul Amira Binti Tahir - Tahir, Nurul Amira (2013)
For over a decade, our world has been facing one of the greatest environmental challenges, which are global warming crisis. Global warming is caused by the emissions of carbon dioxide in the atmosphere. Currently, a large number of servers in our environment waste a lot amount of energy and emit a considerable amount of carbon dioxide. Therefore, green computing has been introduced in order to reduce global warming crisis. To support green computing practices, the System Monitoring Tools version one has been developed which is used to monitor the heat releases from the server. To upgrade the System Monitoring Tools version one, we came out with System Monitoring Tools version two which can calculate the power consumption on the server. In this paper, we propose part of green algorithm which calculates the power consumption use by the CPU. The results show that using green algorithm the power consumption of the server will be calculated and when it reach the benchmark, the system will give alert to the administrator and the server itself will automatically do power management.